The System of Government in The Sultanate of Wadai (1615 – 1900) - Adam, Assadik Ahmad (Journal of Humanities & Social Sciences, 2021)
The aim of the research is to identify how the ruling system prevailing in this vast sultanate, as well as to study and analyze the reality of the ruling system in it, and the purpose of that is to emulate what is qualified for that. The problem of the study is based on the philosophy of the ruling system over the previous centuries, which was adopted in the Valley of the Sultanate of Before its sultans who did a good job in order to advance the sultanate to the best political levels, it turned out that the problem of the research lies in the lack of clarity of the prevailing system of governance adopted by those sultans, so how was the prevailing system of governance in this sultanate? The most important results were as follows: 1- During the reign of its great sultans, the Sultanate of Wadai was able to establish a tight administrative system, which was applied in all the provinces of the Sultanate, which helped in the length of their rule, which lasted for nearly four centuries. 2- Dividing the region into colonels, which included most of the region’s tribes, especially the incoming tribes. 3- The emergence of the impact of Islamic civilization clearly in the Sultanate of Wadai in all the ruling systems followed in the country (the courts, the judiciary, the Imamate, the caliphate, and others).